E-Commerce and Thai Society - Phetcharaburanin, Prisana (Journal of Advanced Development in Engineering and Science, 2023)
Today the world has changed. Information and communication technologies have been developing for many years as well as E-Commerce. So those changes have become an important part of Thai Society. According to research study, e-commerce sector in Singapore and Japan has a dramatically growth in recent year. Both countries have an efficient electronic basic structure and also have an efficient law for E-Commerce sector, those factors are the keys of success in their electronic business. However, Thailand has to face many troubles that need to fix. Thailand still has the inefficient electronic basic structure and law enforcement. Thai ecommerce still has a significant growth and moving to the growth stage.